Organs-on-chips: a decade of innovation. Issue 3 (March 2023) - Strelez, Carly; Jiang, Hannah Y.; Mumenthaler, Shannon M.
Abstract: Recreating 'living organs' with groundbreaking organ-on-a-chip (OOC) technologies is facilitating a new era of drug discovery. Studies by Huh et al. and Ronaldson-Bouchard et al. underscore advances made over a decade, spanning single organ functionality to interconnected organs, that enable examination of drug toxicities and disease pathogenesis in reconstituted tissues.